SOCIO-ECONOMIC EFFECTS OF SEASONAL DOMESTIC WATER SUPPLY AMONG KIBAKU PEOPLE, CHIBOK LOCAL GOVERNMENT AREA, BORNO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
Water is an essential commodity which affects life and livelihoods in the universe. This study examined the socioeconomic effects of seasonal domestic water supply among Kibaku People, Chibok Local Government Area, and Borno State, Nigeria. Random sampling was used to select 165 rural households and water samples for the study. Data collected were analyzed using descriptive and inferential statistics. The significant water sources were hand dug well. The average trekking time to the water source was 10-101 minutes (24.8%). And the households require an average of 162 liters of water per day. The major causes of water scarcity include insufficient rainfall, increased sunlight intensity, pollution of water sources and increased population from the oral interview. About 60% of them stated water scarcity harms their socioeconomic activities as its time consuming (36.1%), causes long queues (48%) and causes conflicts at the point of collection (15.8%). However focus group discussions, interviews and personal observation, respondents believed drinking water is inadequate in Chibok. It was concluded that water available for household use is not sufficient. However, it is safe but contains some elements, not of the World Health Organization standard for good potable water. It is recommended that the community build a hub for water collection and distribution close to the village center. The government should provide water infrastructures to increase the potable water supply
Keywords: Access to water, dry season, rural areas, Sources of Domestic water, water scarcity, water supply